CONCERNING THE NECESSITY OF CHANGE OF TRIMS AGREEMENTS - A. A. Danelуan (Московский журнал международного права, 2018)
Introduction. Developing countries are interested both in the inflow of foreign investments and in their effective use in the country’s economy. To achieve this goal, the recipient states establish in their national legislation investment measures of a commercial nature, which are called “performance requirements” (requirements to achieve certain nationally economically useful results). The interests of foreign investors and recipient states in the issue of measures falling under the term “performance requirements” in most cases do not coincide, as these measures create competitive restrictions for foreign investors related to the use of their capital investments. The possibility for foreign investors to carry out investment activities without execution of investment measures of a commercial nature was one of the main problems of transnational investment. This problem has been resolved in the interests of investment-exporting countries through the adoption of a multilateral TRIMS agreement within the WTO.Materials and methods. The materials for the article were the works of Russian and foreign researchers in the field of international economic law and WTO law as well as the main international legal documents prepared under WTO. The methodological basis of the research consists of general scientific and special methods: dialectical method, methods of analysis and synthesis, deduction and induction, comparative legal and historical legal methods.Research results. The analysis shows that in the doctrine and practice investment measures of a trade nature, e.g. “demand for the export component”, “the demand for currency balance”, “local component requirement”, etc. are known. The Agreement on Trade Related to the Uruguay Round of negotiations under the GATT in 1994 investment measures (TRIMs) limited the ability of states to use “performance requirements”, which, according to the author, is not in the interests of developing countries and does not contribute to their progressive development.Discussion and conclusions. The  author of the article justifies the need to amend the TRIMs Agreement, the purpose of which is to revise the conditions of “performance requirements”.